TRAUMATIC NEUROSIS OF WAR IN COLLIN'S MOCKINGJAY - Muizzu Nurhadi (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2019)
PTSD (Post Traumatic Stress Disoder) is the effects of trauma events that affects the traumatic war survivors. It affects survivor's physical, psyche and mental make the survivors become helpless by overwhelming the force. Mockingjay, one of trilogy of Suzzane Collin's novel presents the traumatic neurosis of war that is depicted in some characters her novel. Therefore, this research is intended to discuss about traumatic effects and traumatic recovery in the novel. In addition, this research applies Herman's psychological trauma to get understanding about the traumatic neurosis of war and stages of traumatic recovery that affect some characters in the novel. This research also uses qualitative method. The discussion is directed through four characters, Katniss; Peeta; Finnick; Johanna, that experience traumatic neurosis of war. The results of the research present that PTSD not only haunts the victims but also the war survivors and traumatic events construct the personality and mental of the survivors.